INFORMATION-PSYCHOLOGICAL INFLUENCES AND INFORMATION-PSYCHOLOGICAL WARFARE AS COMPONENT PARTS OF INFORMATION STRUGGLE - Khoroshko, Volodymyr; Khokhlachova, Yuliia; Pirtskhalava, Tina; Ivanchenko, Yevgeniya (Ukrainian Scientific Journal of Information Security, 2022)
In the present time, which is characterized by the intensive use of various methods of informational, psychological, and technological pressure, which is especially connected with the development of modern technologies that allow to influence the consciousness and psyche of a large number of people at the same time without interaction and direct contact with them, the problem becomes urgent informational and psychological influence (IPVp) on the consciousness of a person, society and the state in various spheres of their life activities. Cyberspace has turned into a separate field of struggle, where various incidents are constantly taking place. In accordance with the purpose, objectives, forms and means of IPVp and information and psychological warfare (IPV), it is necessary to create and ensure countermeasures against them. Uncontrolled use of information space and obtaining significant benefits from its use led to the emergence of fundamentally new related problems. The main one of them was the sharp intensification of international competition for possession of information markets. At the same time, the countries of the world began to actively use the possibilities of the information space (Internet networks) to ensure the information struggle and conduct individual operations. It has been proven that informational and psychological influences are elements of informational struggle-political conflicts in which the political struggle is conducted in the form of informational and psychological operations with the use of informational weapons. At the current stage, science and technology have at their disposal the following theoretical developments on the basis of which the technologicalization of information warfare is carried out. The result is an increase in the effectiveness of the use of information technologies, which has led to drastic changes in society, economy, politics and other spheres of an individual country or on a global scale. Interstate conflicts cause excessively large losses for each of the warring parties. Therefore, the methods that are widely used are only semi-cooperation, mutual competition in development, in the pursuit of leadership. Activities in the information struggle provide opportunities for the use of these approaches.